2004
DOI: 10.2165/00044011-200424070-00004
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Analysis of Relapsing-Remitting Multiple Sclerosis in Italy after the???Introduction of New Disease-Modifying Agents

Abstract: Based on the results of this study, IFNβ treatment considerably modified the management of RRMS and was associated with a rise in cost of treatment per patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Results from a more recent Italian study cannot be compared to our estimates [14]. This study included only patients with RRMS; 75 had an EDSS score <4 and 74 were being treated with DMDs.…”
Section: Discussionmentioning
confidence: 95%
“…Results from a more recent Italian study cannot be compared to our estimates [14]. This study included only patients with RRMS; 75 had an EDSS score <4 and 74 were being treated with DMDs.…”
Section: Discussionmentioning
confidence: 95%
“…In 2004, Kobelt found that in the US DMTs had begun to account for 34% of total costs per MS patient each year, and over half of all direct medical costs [11]. Similarly, an Italian 2004 study suggested that 77% of direct medical costs were attributed to DMTs [12]. On average DMTs cost $16,050 per MS-treated patient per year in 2004 dollars.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the findings of these cost studies may no longer be entirely accurate, since the introduction of new therapies may have changed the management of the disease in several ways. Although more recent cost studies exist, these have focused on specific subgroups of patients treated with DMDs [8,9] or have been performed outside Europe [10], and results cannot be related to the patient population in Europe.…”
Section: Introductionmentioning
confidence: 99%